2017
DOI: 10.1007/s10763-017-9829-z
|View full text |Cite
|
Sign up to set email alerts
|

Designing Learning Environments for Critical Thinking: Examining Effective Instructional Approaches

Abstract: Fostering the development of students' critical thinking (CT) is regarded as an essential outcome of higher education. However, despite the large body of research on this topic, there has been little consensus on how educators best support the development of CT. In view of some of the controversies surrounding the teaching of CT skills in higher education, this study examined the effects of embedding CT instruction systematically in domain-specific courses (Immersion vs. Infusion) on the acquisition of domain-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 45 publications
2
40
0
12
Order By: Relevance
“…It is important to note that the goal of our investigations is to address this process rather than to evaluate a particular teaching environment. In particular, we do not claim to illuminate the much-debated question of which type of instructional intervention would result in better general critical thinking skills [17,42,49].…”
Section: Rationale and Research Questionsmentioning
confidence: 84%
See 1 more Smart Citation
“…It is important to note that the goal of our investigations is to address this process rather than to evaluate a particular teaching environment. In particular, we do not claim to illuminate the much-debated question of which type of instructional intervention would result in better general critical thinking skills [17,42,49].…”
Section: Rationale and Research Questionsmentioning
confidence: 84%
“…In research literature on psychocognition, the question of the possible links between critical thinking and other elements of context is a long debated issue. As summed up by Tiruneh et al [42]: "Whether CT (Critical Thinking) skills are general, domain-transcending set of skills that can be productively applied in any domain, or are specific to a particular domain, has been highly contentious. On the one hand, some scholars [43][44][45] claim the existence of a set of CT skills that are general and applicable across a wide variety of domains such as science, history, literature, psychology, and everyday life, on the ground that CT tasks across domains share significant commonalities.…”
Section: Rationale and Research Questionsmentioning
confidence: 99%
“…The development of CPSPE test was conducted following a test instrument development procedure to measure the thinking and performance skills most of which had been done by researchers [6,7]. The CPSPE test was developed by adapting the general domain of CPS skills found in The Creative Education Foundation [4] into the indicator of CPS skills on photoelectric effect concept.…”
Section: B Discussionmentioning
confidence: 99%
“…Several authors have conducted reviews of the (countless) studies published on this topic [19][20]. On this basis, it has been suggested that explicit initiation in the main principles of critical thinking should be combined with the development of critical analysis within a given field [21]. Here as in previous studies [1], a grounding position is the view expressed by Willingham [17]: 'Critical thinking is not a set of skills that can be deployed at any time, in any context' (p. 10).…”
Section: Students Must Be Prepared To Contend With Ambiguities To Mamentioning
confidence: 99%